Pseudepigraphy and the Petrine school: Spirit and tradition in 1 and 2 Peter and Jude - Chatelion Counet, Patrick (HTS teologiese studies, 2006)
This article identifies four “patterns of religion” (E P Sanders) in the pseudepigraphic letters of Peter and Jude in order to support the hypothesis of a “Petrine school” (J H Elliott). The first pattern that connects the letters is a Geisttradition (K Aland), guaranteeing continuity of tradition. The second is the interrelationship between faith and ethics (fides quae and fides qua). The combination of sanctification and eschatology is a third pattern connecting the three documents. Finally, two florilegia can be identified (one from the Old Testament and apocrypha, and one from the chokmatic tradition), suggesting a fourth pattern: a warning against ungodliness and infidelity. The existence of a Petrine group could represent a preliminary stage of subsequent Early Catholicism.